Differencial proteome of clear-cell renal cell carcinoma (ccRCC) tissues - Ribeiro,Ana Júlia Vieira de (2013)
Purpose We attempted to detect, for the first time in a Brazilian cohort, differences in protein expression between clear-cell renal cell carcinoma (ccRCC) and their normal adjacent tissues, aiming to identify biomarkers and/or therapeutic target candidates for this disease. Material and Methods Twenty-four ccRCC and adjacent normal tissues were collected after surgery and their protein extracts were quantified, pooled and separated by two-dimensional polyacrylamide gel electrophoresis (2DE), followed by statistical analysis of the stained gels. Spots of interest were excised from the gels, digested with trypsin and identified by MALDI-TOF-TOF mass spectrometry. Results Twenty-six differential spots were detected between the two classes of tissues, among which twenty were identified by mass spectrometry and sixteen were found to be non-redundant. Eleven proteins were either underexpressed or undetected in the ccRCC extracts, such as prohibitin and peroxiredoxin-3, whereas five were found to be overexpressed or exclusively detected in the ccRCC extract, including αβ crystalin and heat shock protein 27. CONCLUSIONS Several proteins were detected at differential levels when compared to normal adjacent tissues, and, moreover, many have been previously described by their relationship with RCC. Therefore, this work corroborates previous reports on the search for biomarkers for ccRCC, as well as it points out new candidates that may be validated in future studies.